2014
DOI: 10.1371/journal.pone.0104935
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Evolution and Divergence of SERPINB3: A Young Duplicate in Great Apes

Abstract: A series of duplication events led to an expansion of clade B Serine Protease Inhibitors (SERPIN), currently displaying a large repertoire of functions in vertebrates. Accordingly, the recent duplicates SERPINB3 and B4 located in human 18q21.3 SERPIN cluster control the activity of different cysteine and serine proteases, respectively. Here, we aim to assess SERPINB3 and B4 coevolution with their target proteases in order to understand the evolutionary forces shaping the accelerated divergence of these duplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Post-data filtration, our next strongest hit was a cysteine-protease inhibitor, SerpinB3 (also known as squamous cell carcinoma antigen 1 [SCCA1]), which has known roles in tumor progression in cervical, head and neck cancers, and hepatocellular carcinoma (HCC) ( Cannito et al, 2015 ; Pontisso, 2014 ). SerpinB3 has been observed in the cytoplasm and nucleus of cells and is expressed primarily in the esophagus, nasopharynx, and female reproductive organs in normal human physiology ( Gomes et al, 2014 ; Sun et al, 2017 ; Uhlén et al, 2015 ). We validated the binding of SerpinB3 to His-tagged JAM-A ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Post-data filtration, our next strongest hit was a cysteine-protease inhibitor, SerpinB3 (also known as squamous cell carcinoma antigen 1 [SCCA1]), which has known roles in tumor progression in cervical, head and neck cancers, and hepatocellular carcinoma (HCC) ( Cannito et al, 2015 ; Pontisso, 2014 ). SerpinB3 has been observed in the cytoplasm and nucleus of cells and is expressed primarily in the esophagus, nasopharynx, and female reproductive organs in normal human physiology ( Gomes et al, 2014 ; Sun et al, 2017 ; Uhlén et al, 2015 ). We validated the binding of SerpinB3 to His-tagged JAM-A ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…CTSG and CTSS are genes coding for the proteins cathepsin G and cathepsin S, which belong to the cathepsin family (34), and are involved in the immune response. CTSG and CTSS were revealed to be upregulated by lncRNAs NONHSAT134556.2 and NONHSAT027612.2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent studies showed these two genes are frequently co-expressed in same tissues including bladder, uterus, esophagus, lung, prostate, testis, thymus, and trachea, except SERPINB4 was not detectable in bladder and thymus [14, 30]. The clarification of tissue distribution of these two duplicated proteins benefited from the development of specific antibodies, anti-SERPINB3 (clone 8H11) and anti-SERPINB4 (clone 10C12), which was validated using recombinant proteins [30].…”
Section: Tissue Distributionmentioning
confidence: 99%